Correlation of Intraocular Pressure Reduction and Frequency of Exercise - Sara Listyani Koentjoro; Maharani Cahyono; Fifin Luthfia Rahmi (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Intraocular pressure (IOP) is one of the primary risk factors of glaucoma. It is a modifiablerisk factor and can be affected by exercise. Some studies reported that physical exercise produced IOPreduction. The purpose of this study is to analyze the correlation between IOP reduction and frequencyof exercise.Methods: Thirty seven healthy subjects underwent IOP measurement on both eyes before andimmediately after 5 km of running. The frequency of exercise in a week was recorded and classifiedinto three groups: less than 2 times a week (group 1), 2-3 times a week (group 2), and more than 3times a week (group 3). IOP reductions were calculated and compared between groups. The data wereanalyzed with T-test for each group and ANOVA test for multivariate analysis.Results: There were 30 males and 7 females participated in this study. The mean age was 23.8±6.7years. After running up to 5 km, there was IOP reduction in each group frequency of exercise. Themean IOP reduction in group 1 was 0.20±2.5 mmHg (1.01%), in group 2 was 1.58±2.6 mmHg (8.60%),in group 3 was 1.31±3.0 mmHg (6.82%). IOP reductions in group 2 was statistically significant (p=0.019),compared to the other group. The multivariate analysis of three groups resulted in not significantcorrelation of IOP reduction and frequency of exercise (p=0.431).Conclusion: There was IOP reduction after running up to 5 km in each group frequency of exercise.However, there was no significant correlation of IOP reduction and frequency of exercise. Keywords: intraocular pressure, IOP, exercise